Efficacy Of Triamcinolone Injection In Management Of Oral Lichen Planus - Iqbal, Humera; Luqman, Uzair; Zulfiqar, Kanwal; Rizwan, Zarnab; Zulfiqar, Mobina Fatima (Journal of Rawalpindi Medical College, 2024)
Objective: To study the efficacy of triamcinolone injection in the treatment of oral lichen planus patients presented to the department of oral and maxillofacial surgery at KRL General Hospital Islamabad. Method: This study was conducted in the Department of Oral & Maxillofacial Surgery, Kahuta Research Laboratories Islamabad. 100 patients who fulfilled the inclusion-exclusion criteria were selected. All the enrolled patients were treated with intralesional TA injection once a week for 4 weeks. A 0.5ml TA (40mg/ml) dose was used. The subepithelial tissue just beneath the lesion and next to the normal mucosa was the exact location of the injection. The treatment was stopped earlier when all three of the symptoms of burning, pain and patch colour were removed. The patients were examined clinically on the 7th, 14th, and 21st day of treatment and based on the examination, the decision of the next dose was decided. The final examination of the patient was on the 28th day of treatment. To assess the oral pain and burning, we used the Visual Analogue Scale (VAS) having 10 grades (0-10). Results: The mean age of the patients in the study was 35.47±13.459 ranging from 18 to 65 years. In frequency of gender of the patients, there were 57(57%) male and 43(43.0%) female patients. In frequency of distribution of patients, 38(38.0%) patients had unilateral while the remaining 62(62.0%) had bilateral disorders. In frequency of efficacy, 87(87.0%) patients found with improved symptoms and 13(13.0%) were not improved/inefficient. Conclusion: This study concluded as much of previous literature concluded that the efficacy and safety of intralesional TA injection were found efficient after observation at 28th weeks of treatment. Keywords: Triamcinolone injection, Oral lichen planus, Efficacy, Reticular, Plaque.